Peer Pressure in an Agency Relationship - Barron, John M.; Gjerde, Kathy Paulson (Journal of Labor Economics, 1997)
We investigate the role of peer pressure in influencing the optimal incentive scheme offered to workers engaged in team production. We develop an agency model of peer policing to identify factors that affect the extent of mutual monitoring. As the principal must compensate workers for their monitoring efforts and the costs that peer pressure imposes on workers, introducing peer pressure alters the optimal compensation package. We establish conditions under which the principal reduces the marginal compensation rule to reduce monitoring efforts. As such, peer pressure provides a rationale for a reduced link between compensation and output in a team setting.